Educar para la emancipación : hacia una praxis crítica del sur - Martínez Pineda, María Cristina (CLACSO ; Universidad Pedagógica Nacional, 2020)
We believe that the political-pedagogical and theoretical-conceptual construction that is synthesized in the notion of "critical emancipatory praxis" is tremendously productive for emancipatory education and Latin American critical pedagogies, because it opposes technical, neoliberal and hegemonic conceptions of the educational field and pedagogical; because it recovers the transforming activity of the human being, vindicating the articulation between the understanding and the transformation of reality; because it vindicates the importance of the construction of alternatives for the prefiguration of the society of the future, and therefore, it feeds utopia and hope; because it demands to be affected by the pain and suffering of the other or the other, to be indignant and activate the political exercise of resistance; because it demands the development of political action from below, hand in hand with oppressed peoples, communities and subjects , exploited and excluded.